Baseline urine metabolic phenotype in patients with severe alcoholic hepatitis and its association with outcome. Issue 6 (16th April 2018) - Maras, Jaswinder Singh; Das, Sukanta; Sharma, Shvetank; Shasthry, Saggere M.; Colsch, Benoit; Junot, Christophe; Moreau, Richard; Sarin, Shiv Kumar
Abstract : Urine Acetyl‐L‐carnitine levels identified by high resolution mass spectrometry based metabolomics could identify non‐responders to corticosteroids as early as baseline. Abstract : Severe alcoholic hepatitis (SAH) has a high mortality rate, and corticosteroid therapy is effective in 60% patients. This study aimed to investigate a baseline metabolic phenotype that could help stratify patients not likely to respond to steroid therapy and to have an unfavorable outcome. Baseline urine metabolome was studied in patients with SAH using ultra‐high performance liquid chromatography and high‐resolution mass spectrometry. Patients were categorized as responders (Rs, n = 52) and nonresponders (NRs, n = 8) at day 7 according to the Lille score. Multivariate projection analysis identified metabolites in the discovery cohort (n = 60) and assessed these in a validation cohort of 80 patients (60 Rs, 20 NRs). A total of 212 features were annotated by using metabolomic/biochemical/spectral databases for metabolite identification. After a stringent selection procedure, a total of nine urinary metabolites linked to mitochondrial functions significantly discriminated nonresponders, most importantly by increased acetyl‐L‐carnitine (12‐fold), octanoylcarnitine (4‐fold), decanoylcarnitine (4‐fold), and alpha‐ketoglutaric acid (2‐fold) levels. Additionally, urinary acetyl‐L‐carnitine and 3‐hydroxysebasic acid discriminated nonsurvivors ( P < 0.01). These urinary metabolites significantly correlated to severity indices and mortality ( r > 0.3; P < 0.01) and were associated with nonresponse (odds ratio >3.0; P < 0.001). In the validation cohort, baseline urinary acetyl‐L‐carnitine documented an area under the receiver operating curve of 0.96 (0.85‐0.99) for nonresponse prediction and a hazard ratio of 3.5 (1.5‐8.3) for the prediction of mortality in patients with SAH. Acetyl‐L‐carnitine at a level of >2, 500 ng/mL reliably segregated survivors from nonsurvivors ( P < 0.01, log‐rank test) in our study cohort. Conclusion: Urinary metabolome signatures related to mitochondrial functions can predict pretherapy steroid response and disease outcome in patients with SAH. ( Hepatology Communications 2018;2:628‐643)